2015
DOI: 10.1590/01047760201521041864
|View full text |Cite
|
Sign up to set email alerts
|

Propagação De Erva-Mate Utilizando Brotações De Anelamento E Decepa Em Matrizes De Duas Idades

Abstract: RESUMO A erva-mate é conhecida por seu uso na forma de infusões, como chás e chimarrão. Porém, há um vasto campo de aplicação desta espécie, principalmente na indústria de cosméticos e medicamentos. Um dos fatores limitantes à clonagem comercial de erva-mate é a falta de métodos eficientes de rejuvenescimento de material adulto. Propágulos juvenis podem ser obtidos por meio de anelamento ou decepa de árvores adultas. Desta forma, o objetivo deste trabalho foi verificar a capacidade de enraizamento de estacas o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
1
10
0
2
Order By: Relevance
“…Overall, the stem cuttings used in this study were satisfactory for yerba mate, as observed by other authors (KRATZ et al, 2015;TRONCO et al;STUEPP et al, 2015STUEPP et al, , 2017aSTUEPP et al, , 2017b. The percentage of rooted cuttings ranged from 22.50% to 86.25% among the different treatments.…”
Section: Tablesupporting
confidence: 83%
See 1 more Smart Citation
“…Overall, the stem cuttings used in this study were satisfactory for yerba mate, as observed by other authors (KRATZ et al, 2015;TRONCO et al;STUEPP et al, 2015STUEPP et al, , 2017aSTUEPP et al, , 2017b. The percentage of rooted cuttings ranged from 22.50% to 86.25% among the different treatments.…”
Section: Tablesupporting
confidence: 83%
“…Summary of the variance analysis for the percentage of Ilex paraguariensis rooted cuttings (RC), number of roots per cutting (NR), average root length (ARL), callus (C), cuttings with roots and callus (CRC), mortality (M), sprouts (S) and maintained leaves (LM) in relation to cuttings length at 120 days after planting. Several studies have recommended using semi-hardwood stem cuttings with length patterns of 12 cm and a pair of leaves above the last bud (BITENCOURT et al, 2009;STUEPP et al, 2015STUEPP et al, , 2017aSTUEPP et al, , 2017b. However, we question the lack of papers that corroborate information regarding cuttings smaller than 12 cm and their respective rhizogenic potential, seeing a great discrepancy in studies carried out to date regarding the influence of juvenility and vigor of propagules (BITENCOURT et al, 2009;STUEPP et al, 2015STUEPP et al, , 2017aSTUEPP et al, , 2017b.…”
Section: Tablementioning
confidence: 98%
“…A seleção de matrizes de erva-mate se dá na fase adulta e o primeiro passo é a obtenção de brotações com maior aptidão ao enraizamento adventício. Assim, o desafio é alcançar o sucesso no enraizamento de estacas provenientes destas plantas adultas selecionadas, sem a necessidade de eliminar a planta-matriz (WENDLING et al, 2013;STUEPP et al, 2015). Para isso, são necessários brotos juvenis (BITENCOURT et al, 2009;WENDLING et al, 2013;KRATZ et al, 2015).…”
unclassified
“…Among these, coppicing has shown greater effi cacy in terms of vegetative rescue in Ilex paraguariensis (WENDLING et al, 2013;STUEPP et al, 2015a;, Araucaria angustifolia (WENDLING et al, 2009), Anadenanthera macrocarpa (DIAS et al, 2015) and Toona ciliata (PEREIRA et al, 2015).…”
Section: Epicormic Shoots Inductionmentioning
confidence: 99%
“…However, such method is highly dependent on the regrowth of mother plants capacity and, in certain cases, it turns to be unfeasible due to low vigor. In such cases, the use of techniques such as girdling and partial girdling are recommended, not damaging the plant survival (PEREIRA et al, 2015;DIAS et al, 2015;STUEPP et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%